THE ROLE OF INDUSTRY REGULATIONS IN THE CONSISTENT DEVELOPMENT OF TOURISM - Murodova , N.O. (Eurasian Journal of Academic Research, 2022)
In this article the comparative analysis of development of the tourist sphere is studied. It is proved that the initial periods of independence of the country's leaders and economists did not pay attention to the tourism sector. It is proved that the tourism industry it require little cost, but get a lot of economic and social effects. In recent years, special attention is paid to the tourism industry, timely and periodic regulatory acts. As a result, new jobs are being created and the economic and social spheres of the Republic are developing rapidly.